Mental health literacy as a function of remoteness of residence: an Australian national study - Jorm Anthony F; Christensen Helen; Griffiths Kathleen M (BMC, 2009)
Abstract Background Although there have been many population studies of mental health literacy, little is known about the mental health literacy of people who reside in rural areas. This study sought to determine the impact of remoteness on public knowledge of depression and schizophrenia. Methods The mental health literacy of residents of major cities, inner regional, and outer-remote (including outer regional, remote, and very remote) regions were compared using data from a 2003-04 Australian national survey of the mental health literacy of 3998 adults. Measures included the perceived helpfulness of a range of professionals, non-professionals and interventions, and the causes, prognosis, and outcomes after treatment for four case vignettes describing depression, depression with suicidal ideation, early schizophrenia and chronic schizophrenia. Participant awareness of Australia's national depression initiative and depression in the media, their symptoms of depression and exposure to the conditions depicted in the vignettes were also compared. Results Mental health literacy was similar across remoteness categories. However, inner regional residents showed superior identification of the disorders depicted in the suicidal ideation and chronic schizophrenia vignettes. They were also more likely to report having heard of Australia's national depression health promotion campaign. Conversely, they were less likely than major city residents to rate the evidence-based treatment of psychotherapy helpful for depression. Both inner regional and outer-remote residents were less likely to rate psychologists as helpful for depression alone. The rural groups were more likely to rate the non-evidence based interventions of drinking and painkillers as helpful for a depression vignette. In addition, outer-remote residents were more likely to identify the evidence based treatment of antipsychotics as harmful for early schizophrenia and less likely to endorse psychiatrists, psychologists, social workers and general practitioners as helpful for the condition. Conclusion Mental health awareness campaigns in rural and remote regions may be most appropriately focused on communicating which interventions are effective for depression and schizophrenia and which mental health and other professionals are trained in the best-practice delivery and management of these. There is also a need to communicate to rural residents that alcohol and pain relievers are not an effective solution for depression.